فعالية برنامج تعليمي لتنمية مهارات الحساب لدى الأطفال ذوي طيف التوحد - دامون، إيمان (جامعة الوادي university of Eloued, 2019)
This study aimed at knowing the effectiveness' of am efficacy educational program in developing the skill of calculation for the children with autism spectrum ¸in order to achieve the previous aim¸ the study adopted the semi empirical approach based on the design of a single group with a measurement . The study sample was chosen intentionally ,represented in a case of a single child with autism spectrum at the age of 9, using the achievement test in the calculation module (preparation of the researcher) ,educational program was developed to develop the skill of calculation ,which includes educational and learning goals .then it was applied to child. 1.There are differences in the test grades between the pre measurement grades the autistic child. 2.There are no differences in the test grades between of the post measurement and the sequential measurement of the autistic child.
دراسة حالة بالمدرسة الابتدائية الإمام الغزالي الرباح - الوادي
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: التوحد، البرامج التربوية; Autisme, programmes éducatifs; Autism, educational programs